2019
DOI: 10.1177/0142331219889526
|View full text |Cite
|
Sign up to set email alerts
|

A fuzzy logic-based autonomous car control system for the JavaScript Racer game

Abstract: In this study, we propose a fuzzy logic-based autonomous car control system and its deployment into the JavaScript Racer game. The main design goal of the self-driving car control system is to end up with an intelligent vehicle control system that is capable to keep the car finish race in the shortest time as possible while keeping the car on the road course regardless the road conditions. To accomplish such a design goal, the proposed intelligent driving system takes up and merges the frameworks of control th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…The main advantage of such approach is that it is completely independent of mathematical models, and simulation results showed that this approach can deal with the influence of uncertain factors and obtain higher tracking accuracy. Korkmaz et al [127] designed an autonomous vehicle control system based on fuzzy logic and deployed it into JavaScript racer game. The authors used a simple sliding histogram window approach to detect road lanes and used this information in fuzzy logic reference position and velocity generators.…”
Section: Vehicle Controlmentioning
confidence: 99%
“…The main advantage of such approach is that it is completely independent of mathematical models, and simulation results showed that this approach can deal with the influence of uncertain factors and obtain higher tracking accuracy. Korkmaz et al [127] designed an autonomous vehicle control system based on fuzzy logic and deployed it into JavaScript racer game. The authors used a simple sliding histogram window approach to detect road lanes and used this information in fuzzy logic reference position and velocity generators.…”
Section: Vehicle Controlmentioning
confidence: 99%
“…Historical background on the use of fuzzy logic in general and applications in autonomous vehicle control can be found in Bělohlávek et al (2017) and Driankov and Saffiotti (2001), respectively. A somewhat representative sample of more recent research is seen in Etlik et al (2021), Rastelli and Peñas (2015), and Wang et al (2015).…”
Section: Introductionmentioning
confidence: 99%
“…Historical background on the use of fuzzy logic in general and applications in autonomous vehicle control can be found in (Bělohlávek, Dauben, & Klir, 2017) and (Driankov & Saffiotti, 2001) respectively. A somewhat representative sample of more recent research is seen in (Etlik, Korkmaz, Beke, & Kumbasar, 2021), (Rastelli & Peñas, 2015), and (X. Wang, Fu, Ma, & Yang, 2015).…”
Section: Introductionmentioning
confidence: 99%